P Pengaruh Inovasi Produk, Orientasi Pasar dan Orientasi Kewirausahaan Terhadap Kinerja Pemasaran: Pengaruh Inovasi Produk, Orientasi Pasar dan Orientasi Kewirausahaan Terhadap Kinerja Pemasaran - Bisri, Fauzan; Ika Lis Mariatun; Yusrianto Sholeh (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2023)
Small and medium industries are the first step that can be expected by the government as one of the alternative ways to be able to help the community's economy. The existence of small and medium industries can help the community's economy because it is able to support the economy to meet daily needs. This study aims to determine the influence of product innovation variables, market orientation and entrepreneurial orientation on the marketing performance of small and medium industries convection in Tanah Merah District, Bangkalan Regency. This research is included in quantitative research. The sample in this study amounted to 30 respondents of small and medium industry businesses convection. The data collection process is carried out using questionnaires. In this study, researchers used multiple analysis techniques that were processed using the help of SPSS 25 software. The results of this study show that product innovation and market orientation partially have a significant influence on marketing performance, entrepreneurial orientation partially has no influence on marketing performance and the three variables of product innovation, market orientation and entrepreneurial orientation have a significant as big 33,4% influence on marketing performance.